IoT-based system for monitoring the drying time of date seeds in the manufacturing of date coffee - Jasmine, Arviena; Triawati, Erma (Applied Research and Smart Technology (ARSTech), 2022)
Date palm (Phoenix dactylifera) is a plant of the Phoenix palms whose fruit tastes sweet and can be consumed by humans. These fruit seeds usually only become a waste and never be utilised by people. The research tries to reduce the waste of date palm by using the date palm fruit seeds to replace the coffee beans. One of the processes of changing date palm fruit seeds to coffee beans is drying the seeds. Instead of using a traditional drying method, this study has designed a prototype of an Internet of Things (IoT) based monitoring system tools inside the drying room that allow humidity and temperature sensors, heater, fan, and mixer to be monitored through a smartphone in real-time. Hence, the monitoring tools inside the drying room could be controlled easily, and the data could be saved as databases in smartphone applications.